Sexual Narcissism and the Perpetration of Sexual Aggression - Widman, Laura (2009)
Despite indirect evidence linking narcissism to sexual aggression, studies directly examining this relationship have yielded inconsistent results. Likely contributing to such inconsistencies, prior research has used global measures of narcissism not sensitive to whether the components of narcissism are activated in sexual versus non-sexual domains. The current research avoided such problems by using a measure of sexual narcissism to predict sexual aggression. In a sample of 299 men and women, Study 1 validated the Sexual Narcissism Scale, a new sexuality research instrument with four subscales—Sexual Exploitation, Sexual Entitlement, Low Sexual Empathy, and Sexual Skill. Then, in a sample of 378 men, Study 2 demonstrated that sexual narcissism was associated with reports of the frequency of sexual aggression, three specific types of sexual aggression (unwanted sexual contact, sexual coercion, and attempted/completed rape), and the likelihood of future sexual aggression. Notably, global narcissism was unrelated to all indices of sexual aggression when sexual narcissism was controlled. That sexual narcissism outperformed global assessments of narcissism to account for variance in sexual aggression suggests that future research may benefit by examining whether sexual narcissism and other sexual-situation-specific measurements of personality can similarly provide a more valid test of the association between personality and other sexual behaviors and outcomes (e.g., contraceptive use, infidelity, sexual satisfaction).